Implementation of Tobacco Zakat as an Object of Trade Zakat in Lamongrejo Village, Ngimbang District, Lamongan Regency - Daniswari, Karima; Murni, Murni (Decova Law Journal, 2025)
Zakat plays an important role in the socio-economic order of Indonesia's Muslim-majority society. However, the status of tobacco as an object of zakat is still a matter of debate. This research supports the view of the Hanafi Mazhab followed by Yusuf Qardhawi, which states that tobacco must be zakaah as an economically valuable commodity. Zakat on tobacco is equated with trade zakat because this crop is grown with the aim of being traded. Although tobacco is a high-value commodity in Indonesia's agricultural sector, many farmers do not understand their zakat obligations, especially in the context of trade zakat. This study aims to identify and analyse tobacco farmers' perspectives on tobacco as an object of trade zakat and to find out the implementation of tobacco zakat in Lamongrejo Village. This research uses empirical juridical method, which combines normative approach and field study. The normative approach is conducted by examining legislation and sources of Islamic law, including the Qur'an, hadith, and the views of classical and contemporary scholars regarding tobacco zakat. The empirical approach is applied through interviews. The results show that the majority of farmers in Lamongrejo Village do not understand the obligation of tobacco zakat, and the average farmer in this village has not reached the nisab of trade zakat, so they are not required to pay zakat. However, they are used to paying infaq and alms as a form of gratitude. Further socialisation from religious leaders and zakat institutions on the nisab, haul, and calculation method is needed to improve the community's understanding of tobacco trade zakat. In addition, the establishment of a Zakat Collection Unit (UPZ) in the village is important so that the community can distribute zakat, infaq, and sadaqah according to the Shari'ah.